2004
DOI: 10.1093/glycob/cwh071
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate structure and differential binding of prostate specific antigen to Maackia amurensis lectin between prostate cancer and benign prostate hypertrophy

Abstract: Serum prostate-specific antigen (PSA) assay is widely used for detection of prostate cancer. Because PSA is also synthesized from normal prostate, false positive diagnosis cannot be avoided by the conventional serum PSA test. To apply the cancer-associated carbohydrate alteration to the improvement of PSA assay, we first elucidated the structures of PSA purified from human seminal fluid. The predominant core structure of N-glycans of seminal fluid PSA was a complex type biantennary oligosaccharide and was cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
117
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(128 citation statements)
references
References 28 publications
10
117
1
Order By: Relevance
“…In the same study, we observed a different proportion of alpha 2-3 linked sialic acid in the PSA present in patients, which was decreased in relation to that from healthy seminal plasma (15 vs. 25%) (Tabares et al, 2006). However, our present results are more consistent with the observations made by other authors (Ohyama et al, 2004;Tajiri et al, 2008).…”
Section: N-glycosylation Of Psa 2-de Subforms In Prostate Cancer: Chasupporting
confidence: 92%
See 2 more Smart Citations
“…In the same study, we observed a different proportion of alpha 2-3 linked sialic acid in the PSA present in patients, which was decreased in relation to that from healthy seminal plasma (15 vs. 25%) (Tabares et al, 2006). However, our present results are more consistent with the observations made by other authors (Ohyama et al, 2004;Tajiri et al, 2008).…”
Section: N-glycosylation Of Psa 2-de Subforms In Prostate Cancer: Chasupporting
confidence: 92%
“…These changes in this major subform may be considered representative of the whole PSA, as F3 accounts for 50-70% of all PSA subforms. The percentage of alpha 2-3 sialic acid in seminal plasma PSA was consistent with our previous analyses (25%) (Tabares et al, 2006) and with studies by Ohyama and coworkers (*20%) (Ohyama et al, 2004). In the same study, we observed a different proportion of alpha 2-3 linked sialic acid in the PSA present in patients, which was decreased in relation to that from healthy seminal plasma (15 vs. 25%) (Tabares et al, 2006).…”
Section: N-glycosylation Of Psa 2-de Subforms In Prostate Cancer: Chasupporting
confidence: 92%
See 1 more Smart Citation
“…the content of sialic acid have been elevated on some malignant tumor cells, a positive correlation between cell metastatic potential and total sialic acid content has been reported in many types of tumors. Most of these studies suggested that high level of sialylation may contribute to invasion and metastasis (17)(18)(19). the tumor dissemination is a multistep process involving aberrant biological behavior of tumor cells, such as adhesion, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies observed that a large portion of KLK3 from plasma of prostate cancer patients was non-glycosylated, whereas malignant tumor cells generate KLK3 with more antennae than the common biantennary N-glycan of normal KLK3 (Barak et al, 1989;Prakash and Robbins, 2000). Also, the glycosylation of prostate cancer KLK3 was reduced in benign prostate hyperplasia (BPH) and exhibited a different composition (Basu et al, 2003;Ohyama et al, 2004) KLK3 from prostate tumor cell lines shows an altered sugar composition, with a significant lack of sialic acid in the N-glycan tree (Peracaula et al, 2003). Seemingly, differences exist in fucosylation and sialylation of KLK3 from prostate cancer patients, although they do not appear to be sufficient for reliable prognosis of the disease (Tabares et al, 2006(Tabares et al, , 2007.…”
Section: The Prostatic Klks 2 Andmentioning
confidence: 99%